Rural Development Programme: phase III (1993-1995), appraisal, volume II, anexes - BRAC (© BRAC, 2016)
1. Annex 1: TOR 2. Annex 2: Institution building 3. Annex 3: Sectoral programs & support services 4. Annex 4: Management and training 5. Annex 5: Gender issues 6. Annex 6: Financial analyses 7. Annex 7: Donor liaison office, draft revised, terms of reference